PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS DITINJAU DARI SELF EFFICACY DALAM MATERI ALJABAR PADA SISWA SMP - Soraya, Fitri; Darma, Yudi; Haryadi, Rahman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine whether there is a difference in mathematical problem-solving ability between students who learn using the Problem Based Learning learning model and students who learn with direct learning when viewed from student self-efficacy. The design used is a factorial experimental design. The sampling technique is Cluster Random Sampling. Data collection techniques used are tests, questionnaires and observations. The population in this study were all students of class VIII of SMP Negeri 1 Putussibau. The data collection instruments used were pretest and posttest questions on mathematical problem-solving ability, self-efficacy questionnaires, and teacher and student observation sheets. The analysis used was a two-way ANOVA test with the same cells. Based on the results of the data analysis, it can be concluded that: there is a difference in mathematical problem-solving ability between students who learn using the Problem Based Learning learning model and direct learning, high, medium and low self-efficacy have different mathematical problem-solving abilities, there is no interaction between learning methods and self-efficacy on mathematical problem-solving abilities, meaning that self-efficacy does not depend on learning methods.